Dietary Intake of Omega-3 Fatty Acids and Risk of Depressive Symptoms in Adolescents - Oddy, W.; Hickling, S.; Smith, M.; O'Sullivan, T.; Robinson, M.; de Klerk, N.; Beilin, L.; Mori, T.; Syrette, J.; Zubrick, Stephen; Silburn, S. (Wiley-Liss, Inc, 2011)
Background: Previous randomized controlled trials have demonstrated thatomega-3 polyunsaturated fatty acids (n-3 PUFA) are beneficial in reducingsymptoms of depression. However, there is limited evidence regarding theinfluence of dietary n-3 PUFA intake on mood in adolescents drawn frompopulation studies. Objective: In the present investigation, we examined therelationship between dietary n-3 PUFA intake on depression symptomatology in alarge prospective pregnancy cohort followed for 17 years. Methods: Adolescentsenrolled in theWestern Australian Pregnancy Cohort (Raine) Study completed aFood Frequency Questionnaire to assess dietary fatty acid intake, as well as otherdietary factors at age 14 and a fasting blood sample was taken. Participants alsocompleted the Beck Depression Inventory for Youth (BDI-Y) at age 14(N51,407) and at age 17 (N5995). Results: An inverse relationship wasobserved between intake of both saturated fat and of n-3 PUFA at age 14 andBDI-Y scores at both 14 and 17 years of age. However, after adjusting for energy(kJ) intake and other lifestyle confounders, the relationships were no longersignificant. Conclusions: Associations previously reported between n3 PUFAand depressive symptoms may be due to collinearity with other dietary andlifestyle factors. Depression and Anxiety 28:582–588, 2011. r2011Wiley-Liss, Inc.Key words: omega-3 fatty acids; depression; adolescent; Raine StudyINTRODUCTIONOmega-3